Oral health status and oral health‐related quality of life in children with attention‐deficit hyperactivity disorder and oppositional defiant disorder. (9th January 2021) - Jamali, Zahra; Ghaffari, Parisa; Aminabadi, Naser Asl; Norouzi, Sanaz; Shirazi, Sajjad
Abstract: Aims: Oral diseases can affect various aspects of life in patients with attention deficit hyperactivity disorder/oppositional defiant disorder (ADHD/ODD). This study aimed to assess the oral health status and oral health‐related quality of life (OHRQOL) in ADHD/ODD children. Methods: Forty ADHD/ODD and 80 control children aged 3‐7 years old were included in the study. Gingival index (GI), dmft score, and the pediatric oral health‐related quality of life (POQL) questionnaire were used to determine the oral health status and OHRQOL, respectively. Results: The mean dmft and GI were significantly higher in the ADHD/ODD group than the control group ( P  = .002 and P  = .001). In the ADHD/ODD children, the total score of OHRQOL and the mean scores of the emotional, physical, role, and social domains were lower than that in the control group ( P  = .0004, P  = .027, P  = .002, P  = .014, and P  = .043, respectively). Poisson's regression showed that there was a significant relationship between OHRQOL and dmft scores ( P ‐value < .001). However, the association between GI and OHRQOL scores was not significant. Conclusion: Higher dmft and GI scores were found in children with ADHD/ODD than the control children. A lower POQL score was detected in ADHD/ODD patients, which translates to a better level of OHRQOL.